Assessment of the Impact of Anthropogenic Drainage of Raised Peat-Bog on Changing the Physicochemical Parameters and Migration of Atmospheric Fallout Radioisotopes in Russia’s Subarctic Zone (Subarctic Zone of Russia) - Evgeny Yakovlev; Alexander Orlov; Alina Kudryavtseva; Sergey Zykov; Ivan Zubov (Applied Sciences, 2023)
This paper reports on the research results of the radioactivity levels and upward dispersion of radionuclides of atmospheric fallout 210Pb, 137Cs, 241Am and 234,238U as well as key physicochemical parameters in a peat deposit subjected to drainage in 1969–1971. It was found that drainage of the peat bog led the natural moisture content to shrink in the peat. Active aeration in the peat deposit, accompanied by the growth of Eh, raises the strength of oxidative transformation processes of the organic part of the peat, leading to higher levels of peat degradation and major variations in the elemental content. Changes in these parameters affect the behaviour of radionuclides in the peat section. Thus, in contrast to the sites with a natural hydrological regime, within the dried peat deposit a geochemical barrier of sorption type is not formed, capable of retaining a significant proportion of 137Cs. In this connection, there is an acceleration of 137Cs migration. In addition, changes in the hydrological regime led to the predominance of vascular plants with a more developed root system than that of sphagnum, which also contributed to a more intense transfer of 137Cs by the root system up the section. The findings of 210Pb dating of the dried peat bog showed a significantly lower peat accumulation rate compared to the natural bog massif (0.15 ± 0.02 vs. 0.48 ± 0.08 cm/year). A factor examination of the dataset demonstrated that the leading role in the distribution of radionuclides belongs to redox and acid-base conditions, which have changed significantly after draining the peat deposit.